Gaia Radial Velocity Spectrometer Performance. Issue 67 (17th July 2015) - Cropper, M.; Katz, D.; Sartoretti, P.; Panuzzo, P.; Seabroke, G.; Smith, M.; Dolding, C.; Huckle, H.; Marchal, O.; Benson, K.; Gueguen, A.
Abstract : We present the initial performance of the Gaia Radial Velocity Spectrometer, providing an overview of its performance, which is essentially nominal in terms of spectral resolution, throughput and operation, except for the presence of unexpectedly high levels of scattered background. This is mainly Solar in origin, and reduces the limiting magnitude for radial velocity measurements by ∼1 magnitude to V  ∼ 16. Radial velocity calibration accuracies are compliant with requirements.